Nail Biting as a Cause of Appendicitis - Michael Pagacz; Philip Bao; Juan Carlos Alvarez Moreno; Lydia Howard (Case Reports in Surgery)
Ingestion of a foreign body is commonly encountered in clinical practice, but most cause no complications, passing spontaneously through the gastrointestinal tract. However, they can cause obstructive signs and symptoms, and surgical intervention for extraction of the foreign body may be required after identifying its location. We present here the case of a 49-year-old woman who presented to our emergency room with abdominal pain localizing to the right lower quadrant. Evaluation was most consistent with acute appendicitis, and she underwent uncomplicated appendectomy. A keratin nail with Actinomyces was identified in her appendix. Foreign bodies in the appendix can cause simple appendicitis, perforation, periappendiceal abscess, and peritonitis. Regardless of etiology, an appendectomy often ends up the primary treatment, but unusual and rare causes are worth noting if only for the clinician to be aware of when evaluating the next patient with abdominal pain and considering treatment options or future prevention. Our case is an example of a rare scenario in which an Actinomyces-contaminated human nail lodged in the appendix of a woman eventually resulting in acute appendicitis.